Dopa-responsive dystonia in Chinese patients: Including a novel heterozygous mutation in the GCH1 gene with an intermediate phenotype and one case of prenatal diagnosis. (22nd March 2017) - Zhang, Wen; Zhou, Zhizi; Li, Xiuzhen; Huang, Yonglan; Li, Taolin; Lin, Yunting; Shao, Yongxian; Hu, Hao; Liu, Hongsheng; Liu, Li
Highlights: A novel mutation p.Leu117Arg was identified in GCH1 gene with an intermediate phenotype. Three novel mutations were identified in TH gene. The mutation p.Arg233His may link to the second type of TH deficiency. The mutation p.Arg153X may link to the first type of TH deficiency. Abstract: Dopa-responsive dystonia (DRD) is a rare inherited disorder characterized by childhood-onset dystonia with diurnal fluctuation and dramatic response to levodopa. DRD is caused by the mutations in the genes encoding the enzymes involved in the dopamine and tetrahydrobiopterin (BH4) biosynthesis, including the GTP cyclohydrolase 1 (GCH1) gene and the tyrosine hydroxylase (TH) gene. In order to improve the diagnosis and expand the knowledge of the disease, we collected and analyzed relevant data of clinical diagnosis and molecular mutational analysis in five Chinese patients with DRD. The patients presented with heterogenous symptoms of neurologic disorders. One novel mutation p.Leu117Arg was identified in GCH1 gene with an intermediate phenotype which was predicted in sillico to have a deleterious effect on the GCH1 protein function. Seven different mutations were identified in TH gene including four known mutations: p.Arg233His, p.Gly315Ser, p.Gly247Ser, p.Arg153X, and three novel mutations: p.Arg476Ser, IVS6-34G > C, p.Arg328Gln. The mutation p.Arg233His was predicted to link to the second type of TH deficiency (dopa-responsive infantile parkinsonism with delayed motor development). The mutation p.Arg153X may link to the first type of TH deficiency (typical DRD). The three novel mutations were predicted to be damaging in sillico. A prenatal diagnosis was made in the fourth pregnancy of the parents of patient 2 and proved to be a carrier of a heterozygous mutation. Our study expands the spectrum of genotype of DRD in China, provides new insights into the molecular mechanism of DRD and help to the diagnosis and treatment of this disease.